Adult Environmental Education and the Cultural Commons: A Study of Community Practices for a Just and Sustainable World - Audrey M. Dentith; Emily Kearns Burke; Kris Conmy; Daniel K. Frimpong; Barbara Nadeau; Elizabeth Sanders; Jennifer Saunders; Nancy Winfrey; Sarah Herchel (Adult Education Research Conference, 2014)
Ecojustice adult education, an extension of adult environmental education, has been spurred on by international efforts to educate adults about environmental issues. It is a new and evolving arm of the adult education field that studies the ways that dominant views are impacting human/earth relationships. Ecojustice education teaches about the natural and cultural commons that sustain all life. In this symposiusm, doctoral students investigated their own communities to find examples of the cultural commons.